Potential Tourism Attraction of Cokro Cave, Gunungkidul Regency as a Special Interest Tourism Development - Elisa Dwi Rohani; Muhammad Baiquni; Djoko Wijono; John Soeprihanto (Indonesian Journal of Geography, 2023)
Cave tracing activities have now become a special interest in tourist activities with kars cave as a tracing ground. One of the attractions is because of the physical shape of the cave or what is called (speleotherm). Speleotourism has a charm and experience that is different from other tourist destinations because not all regions in Indonesia have karst areas that are ideal to be developed as Speleo tourism areas, one of which is Gunungkidul Regency which has 5 caves which are geosites, one of which is Cokro Cave.  Cokro Cave was first discovered by nature lovers from the Acintyacunyata Speleological Club (ASC) community in 1993, and in 2009 it began to develop into a tourist attraction managed directly by the local community. This study was conducted to explain how the development of special interest tourism occurred in the tourist attraction of Cokro Cave by utilizing the characteristics and uniqueness of the cave, but still paying attention to the preservation of the cave, as well as the role of local communities, government, and tourism development stakeholders. The concept of special interest tourism that can be applied in the Cokro Cave Area is the management of special interest tourism by limiting the number of visitors to maintain the preservation of the context and collaboration with tourist attractions around and with the Pokdarwis (Kelompok Sadar Wisata) management of the Cave Area. Referring to the six criteria of special interest tourism based on experts, it can be seen that the principles of special interest tourism have not been fully fulfilled in the tourist attraction of Cokro Cave, including no periodic studies on the condition of the cave, as well as monitoring the condition of the cave.